Bis-naphthyl anthracene compound, synthetic method thereof and application of bis-naphthyl anthracene compound in preparation of seawater uranium extraction MOF (30-Zr)

By synthesizing MOF (30-Zr) materials with ultra-high stability performance, the problem of poor stability of metal-organic framework structures in the prior art under seawater conditions is solved, and efficient uranium adsorption effect is achieved, providing seawater with uranium extraction New solution.

CN119306594AActive Publication Date: 2025-01-14CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411351716.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-14
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The existing metal-organic framework structure materials have poor stability under seawater conditions and are difficult to effectively extract uranium from the sea. The existing adsorption materials have slow adsorption speed, poor regeneration ability, and insufficient environmental stability.

Method used

MOF (30-Zr) synthesized by a one-pot method using binaphthalene anthracene compounds and zirconium-containing compounds. This material has ultra-high acid-base and thermal stability, and is improved by modifying the ligand of MOF. Its uranium adsorption capacity.

Benefits of technology

Under simulated seawater conditions, MOF (30-Zr) shows an extremely high uranium adsorption rate of up to 97%, with extremely high adsorption capacity and stability, providing a new direction for seawater uranium extraction materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306594A_ABST
    Figure CN119306594A_ABST
Patent Text Reader

Abstract

The invention relates to the field of extraction of uranium from seawater and new materials, and particularly provides a bis-naphthyl anthracene compound, a synthesis method of the bis-naphthyl anthracene compound and application of the bis-naphthyl anthracene compound to preparation of uranium extraction MOF (30-Zr) from seawater, and the prepared bis-naphthyl anthracene compound is 4-[10-(4-carboxyl naphthalene-1-yl) anthracene-9-yl] naphthalene-1-formic acid (H2NAN). The MOF (30-Zr) with ultrahigh stability is synthesized by taking H2NAN as a ligand and a zirconium-containing compound through a one-pot method, so that the stability of the material is ensured, the material has very high uranium adsorption capacity, and a new direction is provided for using the MOF as a material for extracting uranium from seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of new compounds, new materials and uranium extraction from seawater, and in particular to a dinaphthyl anthracene compound and a synthesis method thereof, and application thereof in preparing MOF (30-Zr) material for uranium extraction from seawater. Background Art

[0002] Uranium, as a core strategic resource of the nuclear energy industry, is mainly obtained through mining. Although the land uranium reserves are about 6.3 million tons, with the continuous growth of energy demand, land uranium resources will be in short supply. The ocean contains about 4.5 billion tons of uranium, which is almost 1,000 times the total amount of uranium available on land. However, the uranium concentration in seawater is relatively low, at 3.3 ppb, so it is necessary to develop effective and economical technology to extract uranium from seawater.

[0003] On the other hand, the continuous development of nuclear power also brings potential hazards to ecological security and human health. Once uranium is released from mining and industrial activities, it will be highly toxic in aqueous solution. Exposure to uranium increases the risk of cancer and / or liver damage, and long-term intake can lead to internal irradiation and chemical toxicity. Therefore, capturing and recovering uranium from aqueous solution is of great significance to human health, environmental protection and the sustainable development of nuclear energy. Existing uranium adsorption materials have some disadvantages in practical applications, such as slow adsorption rate, poor regeneration ability, poor environmental stability, etc. In response to these drawbacks, researchers are constantly exploring new materials and improved processes to improve the efficiency and safety of uranium adsorption and recovery.

[0004] Metal-Organic Frameworks (MOFs) are based on molecular recognition and self-assembly, and are assembled using organic ligands or organic bridges containing special coordinating atoms or coordinating functional groups and metals as building blocks. The rich organic ligands and diverse coordination modes with metal ions / clusters provide unlimited possibilities for the design and synthesis of MOFs. Since its development, MOFs have attracted attention in many fields due to their structural diversity, special pore environment and precise adjustable properties. Although metal-organic framework (MOFs) materials have the characteristics of highly selective adsorption, high specific surface area, environmental friendliness, and strong regeneration ability, there are only more than 300 water-stable MOFs among the more than 100,000 MOFs synthesized so far. Therefore, it is crucial to design and synthesize a MOF material that can adsorb uranium under seawater conditions. Summary of the invention

[0005] In order to solve the problems of poor water, acid and alkali stability of metal-organic framework structures in the prior art, and difficulty in extracting and utilizing uranium from seawater, the present invention prepares a dinaphthyl anthracene compound, a synthesis method thereof, and an application thereof in preparing MOF (30-Zr) for extracting uranium from seawater. The prepared dinaphthyl anthracene compound 4,4'-(anthracene-9,10-diyl)bis(1-naphthoic acid) (H2NAN) is used as a ligand, and a MOF (30-Zr) with ultra-high stability is synthesized by a one-pot method with a zirconium-containing compound. The material has ultra-high acid-base stability and thermal stability, and has high uranium adsorption capacity, which provides a new direction for using MOF as a material for extracting uranium from seawater.

[0006] The present invention first provides a new dinaphthyl anthracene compound, the Chinese name of which is 4-[10-(4-carboxynaphthalene-1-yl) anthracene-9-yl] naphthalene-1-carboxylic acid (abbreviated as H2NAN), and the molecular formula is C 36 H 22 O4, with a relative molecular mass of 518.57, is a yellow solid with the chemical structure:

[0007]

[0008] The present invention further provides a method for preparing the above H2NAN, comprising the following steps:

[0009] S1. Weigh 2.7 g of methyl 4-bromo-1-naphthoate, 2.8 g of bipyraclostrobin, 0.1-0.2 g of [1,1-bis(diphenylphosphino)ferrocene]palladium dichloride and 2.9-3.5 g of potassium acetate, put them into a 500 mL three-necked flask, add 200-300 mL of anhydrous dioxane, react at 80-100 ° C for 1 day under nitrogen environment, cool to room temperature after the reaction, rotary evaporate to dry to obtain a crude product, purify the crude product by column chromatography to obtain product (1);

[0010] S2. The product (1) obtained in step S1, 1.5 g of 9,10-dibromoanthracene, 0.2 g of tetrakistriphenylphosphine palladium and 9.8 g of cesium carbonate were placed in a 500 mL three-necked flask, 200-300 mL of anhydrous dioxane was added, and the mixture was reacted at 80-100° C. for 3 days under a nitrogen environment. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by rotary evaporation to obtain a crude product, and the crude product was purified by column chromatography to obtain a product (2);

[0011] S3. Add the product (2) into a single-necked flask, add 50 mL of 5M sodium hydroxide solution and 100 mL of methanol, and reflux heat at 100°C for 3 days. After the reaction is completed, cool to room temperature, remove methanol, and continue to add deionized water until the solution is clear. Add concentrated hydrochloric acid to the clear solution until pH = 1, filter and vacuum dry to constant weight to obtain the target product (3).

[0012] The reaction equation is:

[0013]

[0014] Based on the above-mentioned binaphthyl anthracene compounds, the present invention also prepares a MOF (30-Zr), and the specific steps are as follows:

[0015] S1. 10 mg of H2NAN, 10 mg of a zirconium-containing compound and 100-300 mg of a modifier were added to 5 mL of solvent, and then 30 microliters of water were added, and ultrasonicated for 10-30 min to form a uniform mixed solution;

[0016] S2. Place the mixed solution obtained in S1 in a 10 mL glass bottle, keep it at 100-130° C. for 24-72 h, filter it, and obtain MOF (30-Zr) crystals.

[0017] S3. The crystals obtained by filtration in S2 are washed, exchanged with acetone and activated to obtain the product.

[0018] Preferably, the zirconium-containing compound is zirconium chloride or zirconium oxychloride octahydrate, and the regulator includes one or more of hydrochloric acid, acetic acid, formic acid, nitric acid, water, methanol, ethanol, and benzoic acid.

[0019] Preferably, the solvent is N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMA).

[0020] Preferably, the MOF (30-Zr) crystals obtained by filtration in S3 are first washed three times with DMF, then washed three times with ethanol, and then soaked in acetone for 24 hours, during which the acetone solution is replaced every 6 hours to complete the acetone exchange of the MOF (30-Zr) crystals.

[0021] As a further preference, the MOF (30-Zr) crystals are exchanged with acetone and then activated at 120° C. for 12 hours.

[0022] The metal-organic framework material MOF (30-Zr) described in the present invention has a molecular formula of [Zr6(O)4(OH)4(NAN)6] n , belongs to the monoclinic Fm-3m space group, in which Zr is a tetravalent zirconium ion, NAN 2-The deprotonated H2NAN ligands are secondary structural units (SBUs) in MOF (30-Zr) and are hexanuclear tetravalent metal clusters [Zr6(O)4(OH)4(COO) 12 ], in which four O ions and four OH ions are coordinated alternately with three Zr ions to form a hexanuclear Zr metal cluster. This SBU is connected by 12 H2NAN ligands, so the overall structure is very stable.

[0023] In summary, the present invention adopts a one-pot method to synthesize MOF (30-Zr) with ultra-high stability and applies it to the field of uranium extraction from seawater. The material is modified with naphthalene anthracene for the ligand on the basis of UiO-68, which not only ensures the stability of the material but also makes the material have a high uranium adsorption capacity. Experiments show that under the conditions of simulated seawater, the MOF has a high uranium adsorption capacity, and its uranium absorption rate can reach 97%, which has extremely high adsorption capacity, and provides a new direction for MOF to be used as a material for uranium extraction from seawater. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : A simplified structural diagram of the MOF (30-Zr) material prepared in Example 5;

[0025] Figure 1 a: six-nuclear cluster of Zr;

[0026] Figure 1 b: Organic ligand of the MOF (30-Zr) material prepared in Example 5;

[0027] Figure 1 c: Structural diagram of the MOF (30-Zr) material prepared in Example 5;

[0028] The cyan color represents the coordination mode of the metal cluster, specifically the connection mode of Zr atoms; the blue color represents the octahedral channels; and the yellow color represents the tetrahedral channels.

[0029] Figure 1 d: Tetrahedral cage of the MOF (30-Zr) material prepared in Example 5;

[0030] Figure 1 e: octahedral cage of the MOF (30-Zr) material prepared in Example 5;

[0031] Figure 2 : Single crystal X-ray simulation image and powder X-ray image of the MOF (30-Zr) material prepared in Example 5;

[0032] Figure 3 : Thermal stability test diagram of MOF (30-Zr) prepared in Example 5;

[0033] Figure 4: H NMR spectrum of the dinaphthyl anthracene compound (H2NAN) prepared in Example 1;

[0034] Figure 5 : Acid-base stability test of the MOF (30-Zr) material prepared in Example 5. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.

[0036] The test methods described in the examples are conventional methods unless otherwise specified; the instruments and materials described are commercially available unless otherwise specified.

[0037] Example 1

[0038] Preparation method of dinaphthyl anthracene compound, 4-[10-(4-carboxynaphthalene-1-yl) anthracene-9-yl] naphthalene-1-carboxylic acid, namely H2NAN:

[0039] The reaction equation is as follows:

[0040]

[0041] The specific steps are:

[0042] S1. Weigh 2.7 g of methyl 4-bromo-1-naphthoate, 2.8 g of bipyraclostrobin, 0.1 g of [1,1-bis(diphenylphosphino)ferrocene]palladium dichloride and 2.9 g of potassium acetate, put them into a 500 mL three-necked flask, add 300 mL of anhydrous dioxane, react at 80-100° C. under nitrogen for 1 day, cool to room temperature after the reaction, and rotary evaporate to dry to obtain a crude product. Purify the crude product by column chromatography to obtain 3.05 g of product (1), with a yield of 97.8%;

[0043] S2. The product (1) obtained in step S1, 1.5 g of 9,10-dibromoanthracene, 0.2 g of tetrakistriphenylphosphine palladium and 9.8 g of cesium carbonate were placed in a 500 mL three-necked flask, 300 mL of anhydrous dioxane was added, and the mixture was reacted at 80-100° C. for 3 days under a nitrogen environment. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by rotary evaporation to obtain a crude product. The crude product was purified by column chromatography to obtain 2.3 g of product (2), with a yield of 95.8%;

[0044] S3. Add the product (2) into a single-necked flask, add 50 mL of 5M sodium hydroxide solution and 100 mL of methanol, and reflux heat at 100°C for 3 days. After the reaction is completed, cool to room temperature, remove methanol, and continue to add deionized water until the solution is clear. Add concentrated hydrochloric acid to the clear solution until pH = 1, filter and vacuum dry to constant weight to obtain 2.1 g of the target product H2NAN, with a yield of 96.3%.

[0045] The target product H2NAN was detected by Figure 4 The HNMR shown can confirm the formation of the compound, and its hydrogen nuclear magnetic resonance spectrum data are: 1H NMR (400 MHz, DMSO-d6): 13.36 (s, 2H), 9.07 (d, 2H), 8.39 (d, 2H), 7.73 (d, 2H), 7.70 (t, 2H), 7.41 (t, 2H), 7.33 (m, 8H) 7.23 (d, 2H).

[0046] Example 2

[0047] Preparation of MOF (30-Zr):

[0048] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 100 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0049] (2) placing the solution in a 10 ml glass bottle, keeping it at 100 °C for 48 hours, and filtering to obtain powdered MOF (30-Zr);

[0050] (3) The MOF (30-Zr) was first washed three times with DMF and then washed three times with ethanol, and then soaked in acetone for 24 hours. During this period, the acetone solution was replaced every 6 hours to complete the acetone exchange of the MOF (30-Zr) crystals. After the acetone exchange, the MOF (30-Zr) crystals were activated at 120°C for 12 hours to obtain MOF (30-Zr).

[0051] Example 3

[0052] Preparation of MOF (30-Zr):

[0053] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 100 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0054] (2) The solution was placed in a 10 ml glass bottle, kept at 110° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0055] Example 4

[0056] Preparation of MOF (30-Zr):

[0057] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 100 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0058] (2) The solution was placed in a 10 ml glass bottle, kept at 120° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0059] Example 5

[0060] Preparation of MOF (30-Zr):

[0061] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 100 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0062] (2) The solution was placed in a 10 ml glass bottle, kept at 130° C. for 48 hours, filtered to obtain crystalline MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0063] Figure 1 The figure shows the structure of the MOF (30-Zr) obtained above, and its molecular formula is [Zr6(O)4(OH)4(NAN)6] n , belongs to the monoclinic Fm-3m space group, see Figure 1 (a), where Zr is a tetravalent zirconium ion, NAN 2- The deprotonated H2NAN ligands are secondary structural units (SBUs) in MOF (30-Zr) and are hexanuclear tetravalent metal clusters [Zr6(O)4(OH)4(COO) 12 ], in which four O ions and four OH ions are coordinated alternately with three Zr ions to form a hexanuclear Zr metal cluster. This SBU is connected by 12 H2NAN ligands, so the overall structure is very stable.

[0064] Figure 2Shown are the single crystal X-ray simulation image and powder X-ray image of the MOF (30-Zr) material obtained above. It can be seen from the figure that the peak positions of the simulated and tested curves are consistent, indicating that the material has extremely high purity.

[0065] Figure 3 The thermal stability test diagram of the MOF (30-Zr) obtained above is shown. The figure shows that the mass slowly decreases in the range of 30-400°C due to the removal of solvent molecules in the pores of the material. After 500°C, the mass decreases rapidly due to the structural collapse of the material. The figure shows that the material has extremely high thermal stability, and its highest thermal stability temperature is 500°C.

[0066] Example 6

[0067] Preparation of MOF (30-Zr):

[0068] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 200 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0069] (2) The solution was placed in a 10 ml glass bottle, kept at 100° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0070] Example 7

[0071] Preparation of MOF (30-Zr):

[0072] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 200 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0073] (2) The solution was placed in a 10 ml glass bottle, kept at 110° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0074] Example 8

[0075] Preparation of MOF (30-Zr):

[0076] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 200 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0077] (2) The solution was placed in a 10 ml glass bottle, kept at 120° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0078] Example 9

[0079] Preparation of MOF (30-Zr):

[0080] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 200 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0081] (2) The solution was placed in a 10 ml glass bottle, kept at 130° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0082] Example 10

[0083] Preparation of MOF (30-Zr):

[0084] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 300 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0085] (2) The solution was placed in a 10 ml glass bottle, kept at 100° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0086] Embodiment 11

[0087] Preparation of MOF (30-Zr):

[0088] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 300 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0089] (2) The solution was placed in a 10 ml glass bottle, kept at 110° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0090] Example 12

[0091] Preparation of MOF (30-Zr):

[0092] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 300 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0093] (2) The solution was placed in a 10 ml glass bottle, kept at 120° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0094] Embodiment 13

[0095] Preparation of MOF (30-Zr):

[0096] (1) 10 mg of H2NAN, 10 mg of zirconium chloride and 300 mg of benzoic acid were added to 5 ml of DMF and 30 μl of water, and ultrasonicated for 10 minutes to form a uniform mixed solution;

[0097] (2) The solution was placed in a 10 ml glass bottle, kept at 130° C. for 48 hours, filtered to obtain powdered MOF (30-Zr), and then washed, solvent exchanged, and activated by the same method as in Example 2 to obtain MOF (30-Zr).

[0098] Experimental Example 1

[0099] Water, acid and alkali stability test of MOF (30-Zr):

[0100] The activated MOF (30-Zr) in Example 5 was divided into 7 portions (10 mg each), and placed in 10 ml glass bottles respectively. 5 mL of aqueous solution (pH = 1, 3, 5, 7, 9, 11, 13) was added to the corresponding solution (pH was adjusted with sodium hydroxide and hydrochloric acid) and soaked for 7 days. After soaking, the mixture was centrifuged and dried, and powder X-ray diffraction analysis was performed. The test results are shown in Table 1. Figure 5 The experiment shows that within the pH range of 1-11, the peak position and peak intensity of XRD do not change significantly. The material has high water, acid and alkali stability, and its stable range is pH 1-11.

[0101] Experimental Example 2

[0102] Test of uranium adsorption by MOF (30-Zr):

[0103] The uranium adsorption experiments were carried out in pure water with a pH of 7 and simulated seawater with a pH of 8.3 (30 g of sea salt was prepared into 1 L of simulated seawater with water).

[0104] In a typical process, 10 mg of MOF (30-Zr) prepared in Example 5 was added to 10 mL of 15 ppm uranyl nitrate hexahydrate solution (prepared with pure water and simulated seawater, respectively). The solution was stirred magnetically (600 rpm) for 1 h at room temperature (about 23 ° C), the adsorbent was separated by centrifugation, and the supernatant was analyzed for uranium concentration by UV-visible spectrophotometer. Arsenazo III dye has a strong absorption band at 652 nm as a complexing agent for uranium. The specific experimental data are as follows.

[0105]

[0106] Experiments show that under conditions simulating seawater, the MOF has a high uranium adsorption capacity, with a uranium absorption rate of up to 97%, which has extremely high adsorption capacity.

[0107] It can be seen that the present invention synthesized a MOF (30-Zr) with ultra-high stability and applied it in the field of uranium extraction from seawater. The material modified the ligand on the basis of UiO-68, which not only ensured the stability of the material but also made the material have a high uranium adsorption capacity, providing a new direction for MOF to be used as a material for uranium extraction from seawater.

[0108] Experimental Example 3

[0109] The MOF (30-Zr) in Example 5 was measured by single crystal X-ray diffraction. The crystal data, bond length and bond angle of MOF (30-Zr) (Example 5) are shown in Tables 1-3 below. The structure of MOF (30-Zr) belongs to the monoclinic Fm-3m space group, and its unit cell parameters are the axial length Axis angle α = 90.000°, β = 90.000°, γ = 90.000°, unit cell volume is

[0110] Table 1: Crystal data

[0111]

[0112]

[0113] Table 2: Typical bond length data of crystals (unit: )

[0114]

[0115]

[0116] Table 3: Typical bond angle data of crystals (unit: °)

[0117]

[0118]

Claims

1. A dinaphthyl anthracene compound, characterized in that: Its Chinese name is 4-[10-(4-carboxynaphthalen-1-yl) anthracene-9-yl] naphthalene-1-carboxylic acid, and its molecular formula is C 36 H 22 O4, with a relative molecular mass of 518.57, is a yellow solid with the chemical structure:

2. The method for synthesizing the binaphthyl anthracene compound according to claim 1, characterized in that: The following steps are involved: S1. Weigh 2.7 g of methyl 4-bromo-1-naphthoate, 2.8 g of bipyraclostrobin, 0.1-0.2 g of [1,1-bis(diphenylphosphino)ferrocene]palladium dichloride and 2.9-3.5 g of potassium acetate, put them into a 500 mL three-necked flask, add 200-300 mL of anhydrous dioxane, react at 80-100 ° C for 1 day under nitrogen environment, cool to room temperature after the reaction, rotary evaporate to dry to obtain a crude product, purify the crude product by column chromatography to obtain product (1); S2. The product (1) obtained in step S1, 1.5 g of 9,10-dibromoanthracene, 0.2 g of tetrakistriphenylphosphine palladium and 9.8 g of cesium carbonate were placed in a 500 mL three-necked flask, 200-300 mL of anhydrous dioxane was added, and the mixture was reacted at 80-100° C. for 3 days under a nitrogen environment. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by rotary evaporation to obtain a crude product, and the crude product was purified by column chromatography to obtain a product (2); S3. Add the product (2) into a single-necked flask, add 50 mL of 5M sodium hydroxide solution and 100 mL of methanol, and reflux at 100°C for 3 days. After the reaction is completed, cool to room temperature, remove methanol, and continue to add deionized water until the solution is clear. Add concentrated hydrochloric acid to the clear solution until pH = 1, filter and vacuum dry to constant weight to obtain the target product (3); The reaction formula is as follows:

3. The use of the binaphthyl anthracene compound according to claim 1 in the preparation of MOF (30-Zr) for extracting uranium from seawater, characterized in that: The specific steps for synthesizing MOF (30-Zr) are as follows: S1. 10 mg of the binaphthyl anthracene compound, 10 mg of the zirconium-containing compound and 100-300 mg of the modifier were added to 5 mL of solvent, and then 30 microliters of water were added, and ultrasonicated for 10-30 min to form a uniform mixed solution; S2. The mixed solution obtained in S1 is kept at 100-130°C for 24-72h and filtered; S3. The crystals obtained in S2 are washed, exchanged with acetone and activated to obtain the product.

4. The use of the binaphthyl anthracene compound according to claim 3 in the preparation of MOF (30-Zr) for extracting uranium from seawater, characterized in that: The zirconium-containing compound is zirconium chloride or zirconium oxychloride octahydrate.

5. The use of the binaphthyl anthracene compound according to claim 3 in the preparation of MOF (30-Zr) for extracting uranium from seawater, characterized in that: The regulator includes one or more of hydrochloric acid, acetic acid, formic acid, nitric acid, water, methanol, ethanol, and benzoic acid.

6. The use of the binaphthyl anthracene compound according to claim 3 in the preparation of MOF (30-Zr) for extracting uranium from seawater, characterized in that: The solvent is N,N-dimethylformamide or N,N-dimethylacetamide.

7. The use of the binaphthyl anthracene compound according to any one of claims 3 to 6 in the preparation of MOF (30-Zr) for extracting uranium from seawater, characterized in that: After MOF (30-Zr) was prepared and obtained by the S1 and S2 methods, the MOF (30-Zr) crystals were first washed three times with DMF, then washed three times with ethanol, and then soaked in acetone for 24 hours, during which the acetone solution was replaced every 6 hours to complete the acetone exchange of the MOF (30-Zr) crystals.

8. The use of the binaphthyl anthracene compound according to claim 7 in the preparation of MOF (30-Zr) for extracting uranium from seawater, characterized in that: MOF (30-Zr) crystals were exchanged with acetone and activated at 120 °C for 12 h.

Citation Information

Patent Citations

  • Method for using metal-organic framework material to purify water, exchange ions with water or magnetize water

    CN102249363A

  • Carboxyl functionalized ionic single crystal material for extracting uranium from seawater and preparation method of carboxyl functionalized ionic single crystal material

    CN118440342A